What the Catholic Church Has Learnt from Interreligious Dialogue - Fitzgerald, Michael L. (Studies in Christian-Jewish relations, 2005)
Archbishop Michael L. Fitzgerald, M.Afr. until recently served as the president of the Pontifical Council for Interreligious Dialogue in the Vatican. In February 2006 he was appointed by Pope Bendedict XVI to be the apostolic nuncio to Egypt and the Holy See's delegate to the League of Arab States. This address was delivered at the conference "In Our Time: Interreligious Relations in a Divided World," co-sponsored by the Center for Christian-Jewish Learning at Boston College and Brandeis University to mark the 40th anniversary of Nostra Aetate. It was given at Brandeis University on March 16, 2006. In it, Archbishop Fitzgerald first discusses theological advances arising from interreligious dialogue, focusing on the interrelatedness of the Trinity as the basis and model for dialogue. He then turns to consider the necessary conditions for dialogue, the varied content of dialogue, the conduct of dialogue in its multiplicity of forms, and the structures necessary for the continuity of dialogue.